"Compañeros del batallon "Libertad" de la CNT con sus fusiles en manos". Copied from CNT collection. Series from 2 photos
"Compañeros del batallon "Libertad" de la CNT con sus fusiles en manos". Copied from CNT collection. Series from 2 photos.